Teriparatide improves alveolar bone modelling after tooth extraction in orchiectomized rats - de Oliveira Puttini, Igor [UNESP]; Gomes-Ferreira, Pedro Henrique da Silva [UNESP]; de Oliveira, Danila [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Gonçalves, Paulo Zupelari [UNESP]; Okamoto, Roberta [UNESP] (Elsevier, 2019)
Objective: The aim of this study was to evaluate bone metabolism in the alveolar repair process in orchiectomized male rats treated with teriparatide. Materials and methods: A total of 78 rats were divided into three groups: 26 oriectomized rats treated with teriparatide (ORQTRAT), 26 untreated orchiectomized rats (ORQ), and 26 rats which had undergone sham surgical procedures (SHAM), all these animals underwent extraction of the central incisor tooth. Thus, a histological analysis was performed (42 days). Real Time PCR (14 and 42 days) and immunohistochemical (42 days) analyses were performed based on the expression of RANK-L and osteoprotegerin (OPG). The calcein and alizarin were analyzed via laser confocal microscopy to verify alveolar bone turnover, and microtomographic analysis was performed to determine volume and bone quality (calcified tissues). In this analysis, the euthanasia period was 60 days post-extraction. The quantitative data were submitted to the statistical test and the significance level of 5% was adopted. Results: Teriparatide increased bone turnover with a higher relative gene expression of RANKL and OPG at 14 days, and at 42 days, there was a significant decrease of RANKL and an increase of OPG, this standard can also be evaluated in the ratio of RANKL to OPG. Greater values of area and bone mineral deposition were found for the ORQTRAT group (p < 0.05), along with higher bone volume values (p < 0.05). The immunolabels revealed greater intensity in the relationship of RANKL and OPG, which led to intense remodeling aiding in the process of bone formation. Conclusion: The teriparatide treatment in orchiectomized rats increases bone volume and decreases the porosity, in addition to promoting greater intensity in bone turnover during alveolar repair.
Keywords: Bone and bone; Men; Osteoporosis; Parathyroid hormone (1-34) amide; Teriparatide